MENGEMBANGKAN KREATIVITAS ANAK USIA DINI MELALUI KEGIATAN KOLASE MENGGUNAKAN MEDIA AMPAS KELAPA - Siti Nur Laelliah; Fitria Ayu Febriani; Mintarsih; Siti Syfa Filzannah; Sri Wati; Evy Fitria (LPPM Universitas Cipta Mandiri, 2025)
Collage activities using natural materials, such as coconut pulp, are an interesting and effective method for developing creativity in early childhood. Coconut pulp, as an easily accessible, environmentally friendly, and safe natural material for children, provides them with the opportunity to explore various textures, shapes, and colors. In addition, the use of natural media can introduce the concept of recycling and environmental awareness from an early age. This study aims to develop early childhood creativity through collage activities using coconut pulp. The research method used is classroom action research, conducted in three cycles. Each cycle consists of planning, observation, and reflection. The subjects of this study were eight children aged 5-6 years in Class B at KB At Thohiriah Pasar Kemis, Tangerang Regency. The results of the study showed that children's creativity improved when provided with collage media made from coconut pulp. The increase in children's creativity also grew as they were given the freedom to explore and draw freely, in line with their imagination and desires.